2018
DOI: 10.3389/fnsys.2017.00097
|View full text |Cite
|
Sign up to set email alerts
|

Differential Influence of Early Life and Adult Stress on Urogenital Sensitivity and Function in Male Mice

Abstract: Experiences of adverse childhood events have been associated with improper output of the hypothalamic-pituitary-adrenal (HPA) axis in adulthood, as well as development of comorbid functional pain disorders. Symptoms of chronic prostatitis/chronic pelvic pain syndrome frequently overlap with those of interstitial cystitis/painful bladder syndrome and symptom severity is often triggered by stress. The objective of this study was to investigate the influence early life stress and acute adult stress on (1) perigen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
34
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(44 citation statements)
references
References 71 publications
8
34
2
Order By: Relevance
“…Importantly, a history of being physically active, particularly having a higher level of moderate-and high-intensity physical activity, was associated with a lower risk of developing CP/CPPS in older men (67) and endometriosis in young adult women (68). Here, we report that male NMS mice display significant mechanical allodynia in the perigenital region, a finding that supports our previous research (45). Allodynia in the perigenital or pelvic region has been consistently reported in other mouse models of CP/CPPS (19,69).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Importantly, a history of being physically active, particularly having a higher level of moderate-and high-intensity physical activity, was associated with a lower risk of developing CP/CPPS in older men (67) and endometriosis in young adult women (68). Here, we report that male NMS mice display significant mechanical allodynia in the perigenital region, a finding that supports our previous research (45). Allodynia in the perigenital or pelvic region has been consistently reported in other mouse models of CP/CPPS (19,69).…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with our previous studies (39,45), NMS induced significant perigenital hypersensitivity ( Figure 2). Sedentary NMS mice exhibited significantly lower withdrawal thresholds in response to mechanical, monofilament stimulation to the scrotum compared to their naïve-Sed counterparts.…”
Section: Voluntary Wheel Running Prevented Nms-induced Perigenital Hysupporting
confidence: 92%
See 1 more Smart Citation
“…Although running distance was significantly lower, we have observed an attenuation of urogenital hypersensitivity and bladder overactivity due to voluntary wheel running in female NMS mice [47]. We hypothesize that differences in running distance could be due to changes in reward pathways, as we have also observed gene expression changes indicative of reduced hippocampal regulation of the HPA axis [27,28,47,73]. Lovallo [74], explains that early life stress in humans can lead to altered dopaminergic signaling, which influences motivated behaviors [75], including physical activity.…”
Section: Discussionmentioning
confidence: 77%
“…A previous study showed that about one-third of rats exposed to NMS but none in the control group retained perigenital reflex at 7 wk old suggesting an incomplete maturation of voiding control in the NMS animals (38), which agrees with the findings in this study. More recent studies demonstrated that 1) NMS mice had a significantly higher sensitivity upon urinary bladder distension in adulthood compared with the control group, 2) the hypersensitivity to urinary bladder distension mice was further increased after exposure to water avoidance stress in adult NMS mice but not in control mice, and 3) NMS mice had an increase in the number of voids compared with the control mice at 8 wk old (19,29,30). These results suggest the effects from NMS on bladder sustained in young adulthood, which also support our findings.…”
Section: Discussionmentioning
confidence: 99%